Restoration of the endodontically treated posterior tooth - Andrea Polesel (Ariesdue, 2014)
Objectives: To analyse the key factors of the restoration in the posterior endodontically treated teeth, through a literature review and clinical cases presentation. To focus on the clinical advantages of the adhesive indirect restorations, describing the basic principles for long-term success. Materials and methods: The biomechanical changes due to the root canal therapy and the degree of healthy dental tissue lost because of pathology and iatrogenic factors are the critical points leading the clinician to the restorative treatment planning. The full crown is considered by the literature as the gold standard and is indicated in case of teeth heavily weakened by dental caries, fractures or previous conservative-prosthetic preparations. The improvement of the adhesion and the composite materials, with mechanical properties close to those of dental tissues, offers to the clinician the option of a conservative restoration, able to seal, reinforce and protect the tooth and to delay the execution of a full crown, with the subsequent sacrifice of dental tissue. Although in the presence of small-sized cavity, direct bonded restoration is considered an effective short and medium-term restoration, cuspal coverage with indirect restoration is the treatment of choice in case of mesio-occlusal-distal cavities. Adhesive overlays preserve coronal structure, avoid contamination of the root canal system, reinforce residual dental tissues, guarantee optimal form, function, aesthetics and offer ergonomic and economic undoubted clinical advantages. Results and conclusions: Direct adhesive restorations, indirect bonded restorations and traditional full crown are three therapeutic options for the single posterior endodontically treated teeth. The amount of remaining sound tooth structure is the most significant factor influencing the therapeutic approach. The clinician's operative skill is a determining aspect for long-term success of adhesive inlays.